The concept of human trafficking: theoretical and legislative aspects - Kyzdarbekova, B.Zh. (Publ.KarSU, 2017)
The article studies modern approaches to the definition of the concept of «human trafficking» and its generative features in scientific literature, international law and Kazakhstan's criminal legislation. The concept of «human trafficking», consolidated in p. 1 of the Art. 128 of the Criminal Code of the Republic of Kazakhstan, for compliance with its similar definition in the Palermo Protocol. On the basis of available scientific developments’ comprehension, a further comprehensive study of the content of such conceptual features of human trafficking as other transactions in relation to a person, his/her purchase, sale, exploitation, recruitment, transportation, transfer, harboring and receipt was carried out. Based on the results of the study, the author came to the conclusion that the position of scientists, according to which the concept of trafficking covers a wider range of unlawful acts, is consistent with the norms of international and domestic legislation; current edition of the disposition of the Art. 128 of CC RK, having a number of unconditional advantages, requires adjustments and changes. The allocation of concealment as an independent act of human trafficking is questioned. The author makes suggestions on the improvement of the legislative definition of the concept of «human exploitation ».
Адам саудасының түсінігі жəне нысандары: теориялық жəне заңнамалық аспектілері
Понятие и формы торговли людьми: теоретический и законодательный аспекты
Keywords: Human trafficking; crime against the person; concept of human trafficking; object of human trafficking; elements of human trafficking; sale and purchase of human; human exploitation; recruitment faces; slavery; slavery